A review on the trend of livestock breeds in Laos - Xayalath, Somsy; Mujitaba, Malam Abulbashar; Ortega, Art David Sol Valmoria; Rátky, József (Acta Agraria Debreceniensis, 2021)
When the livestock sector is considered an essential role in farmers’ livelihood, and local breeds are still the critical component of animal breeding in Laos. Thus, there is a need to review the previous, current situation and prospects for Laos’ livestock production. It aimed to study the different traits among the existing dominant local and improved livestock breeds (cattle, pig, and goat) and a more in-depth study on the livestock sector’s previous evolving and prospects. Our findings revealed that the general trend of livestock population in Laos increased year-by-year for over 45 years, except for 1995 to 2000. It was decreased by almost 22% due to the new national strategy on economic revolution. The first foreign breeds were introduced into Laos, i.e., Large White, Landrace, and Duroc in 1980, Red Sindhi bulls in 1998, the frozen semen of Red Brahman 2003, and Bach Thao goats between 2001 to 2003. Unfortunately, many data are still not precise for introducing other foreign breeds like Boer goats, Thai Grey and Red Brahman. There were many missing data on the improvement of livestock breeds in Laos, including the local and improved breeds’ reproductive and productive performance, which needs more study and research. We conclude that the semi-complex farm operation should be applied to improve livestock breeding and their productions in Laos.